Viscosity reduction of water-in-oil emulsion by phase inversion: surfactants performance and characterization - Nascimento Nariyoshi, Yuri; Meneguelo, Ana Paula; de Castro Santana, Rejane (Latin American Journal of Energy Research, 2024)
The phase inversion technique has received attention in the petroleum industry in order to decrease energy consumption. Crude oil emulsions with model brine solutions containing 1.5% wt NaCl and 1.0 wt.% surfactants were produced and evaluated on electrical conductivity, kinetic stability, microstructure and rheology. It was found that phase inversion occurred in the range of 20-40 wt.% of brine. Emulsions having 10-40 wt.% of brine and Triton-X-100 manifested lower phase separation than without surfactant or with Tween 80, while oil-in-water emulsions having 50 and 60 wt.% of brine and Triton-X-100 achieved the lowest value of viscosity. Thus, these results elucidate the influence of selected parameters on emulsions properties aiming to improve mobility and flowability by phase inversion of high viscous water-in-oil emulsion.
Keywords: crude oil; rheology; phase transition; kinetic stability; Triton-X-100; Tween 80